2002
DOI: 10.1080/00291950260293048
|View full text |Cite
|
Sign up to set email alerts
|

Burning for zebu: The complexity of deforestation issues in western Madagascar

Abstract: This study takes a human-geographica l approach to examine the crucial problem of deforestation in Madagascar. Current land-use practices on the west coast threaten the survival of the dry primary forest, which exists in a delicate ecologica l balance under a climate bordering on aridity. A shifting-agricultur e system, encouraged by government policy aimed at expanding crop cultivation , is the major factor contributin g to the reduction of forested land. The forest is set on re and the burns used to cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 7 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…However, we found that locusts destroyed ~80% of the maize harvest in 2014. In addition, maize is one of the major drivers of deforestation in southern Madagascar (Réau 2002, Minten et al 2010). This clearly shows that current development agendas suffer from a too limited view of how contemporary social-ecological systems on the Mahafaly Plateau operate.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that locusts destroyed ~80% of the maize harvest in 2014. In addition, maize is one of the major drivers of deforestation in southern Madagascar (Réau 2002, Minten et al 2010). This clearly shows that current development agendas suffer from a too limited view of how contemporary social-ecological systems on the Mahafaly Plateau operate.…”
Section: Resultsmentioning
confidence: 99%
“…While it may be scarce, analysis of the repeat photographs shows that in many areas endemic woody vegetation has been stable over the past century. This is in sharp contrast to the dramatic deforestation ravaging the eastern rainforest (Green & Sussman 1990) and parts of the western dry forests (Réau 2002). It should be noted, however, that 12 of the 19 photo pairs with natural woody vegetation occur in just two specific ecological zones, so generalization to all forms of native woody vegetation is not warranted.…”
Section: Natural Forest and Woody Vegetationmentioning
confidence: 96%
“…Moreover, restricting privatization of samata parcels does not fit with the traditional ideology that clearing, marking or fencing land legitimates its ownership. Thereby, cleaning for subsistence activities has the same legitimacy as cleaning for privatizing samata or cultivating other cash crops (Réau 2002).…”
Section: Reasons For the Failure To Implement The Curtailmentmentioning
confidence: 99%